The cost of soil erosion in sub-Saharan Africa: Insights for policy - Bolo, Peter; Kinyua, Michael; Waswa, Boaz; Kihara, Job (2025)
Soil erosion is an urgent environmental concern. Nearly 494 million hectares in sub-Saharan Africa (SSA) are experiencing some form of land degradation. Of these, about 227.4 million hectares (i.e., 46%) are affected by water erosion, wind erosion (186.5 million; 38%), loss of nutrients via chemical degradation (12 %), and physical deterioration (4%). With losses of about 50 kg of nitrogen (N), phosphorus (P), and potassium (K) per hectare per year, and 50–66% of yield – costing SSA approximately USD 68 billion annually – soil erosion impacts the socio-economic wellbeing of millions of households across SSA. Regenerating degraded soils and building soil health is critical for sustainable food systems transformation. Across Africa, agriculture needs to aim for zero erosion and runoffs by embracing complementary soil management practices (e.g., combined conservation agriculture and integrated soil fertility management -ISFM), and structural measures (e.g., contour farming, terracing, and zai pits). Policy efforts should focus on provisioning incentives for long-term sustainable management efforts against soil erosion through complementary soil management interventions and supporting farmers and other stakeholders with enabling conditions for implementing appropriate agriculture practice bundles (see section on Policy Intervention Areas).